Communicative English Language Teaching Methodology: The Importance of Communication in Modern Approaches - Aytmuratova Parwaz Qoshqarbaevna; Shniqulova Uldawlet Jumabaevna (Periodica Journal, 2024)
This article examines the role and effectiveness of communicative language teaching (CLT) in learning English. Grounded in modern pedagogical approaches, CLT facilitates practical language acquisition through communication, allowing learners to engage in direct interaction. This paper highlights communication-centered teaching methods, the role of technology in this process, and how these techniques can be applied in practice. The study demonstrates that CLT actively engages learners, enhances motivation, and creates opportunities for real-life language application, making language acquisition both effective and enjoyable
Keywords: communicative language teaching; English teaching methodology; interactive learning